Responsibility Assignment in Systems Engineering - Gräßler, Iris; Thiele, Henrik; Grewe, Benedikt; Hieb, Michael (Proceedings of the Design Society)
Abstract Increasing system complexity can be controlled by using systems engineering processes. INCOSE defines processes with inputs and outputs (artifacts) for this purpose. Specific SE roles are used to organize the tasks of the processes within the company. In this work, the responsibilities for artifacts are evaluated by means of the RACI scheme and examined by a cluster analysis and discussed for a SE transformation project with a German automotive OEM. As a result of the study, the optimal composition for systems engineering teams is identified and the systems engineering roles are prioritized.
Keywords: systems engineering (SE); project management; model-based systems engineering (MBSE)